PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT, KUALITAS PELAYANAN, DAN KEPERCAYAAN TERHADAP RETENSI PASIEN MELALUI KEPUASAN PASIEN DI RUMAH SAKIT KOTA MEDAN - Jenny Nurani Hutasoit; Maykhael Bernandus Gultom; Rizky Sanjaya Nainggolan; Anita Christine Sembiring (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
Customer Relationship Management (CRM) is a crucial strategy for retaining customers and preventing them from switching to competitors. This study examines the effects of CRM, service quality, and trust on patient retention through patient satisfaction among inpatients using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results indicate that the measurement model satisfies the required reliability and validity criteria. The coefficient of determination (R²) is 0.404 for patient satisfaction and 0.554 for patient retention, indicating moderate to substantial explanatory power. CRM and service quality have positive and significant effects on both patient satisfaction and patient retention, whereas trust has no significant effect on either variable. Patient satisfaction significantly influences patient retention but does not mediate the relationships between CRM, service quality, trust, and patient retention. These findings highlight the importance of strengthening CRM implementation and improving service quality to enhance BPJS inpatient retention and foster long-term patient loyalty.